The impact of jumping during recovery on repeated sprint ability in young soccer players - Padulo, J.; Tabben, M.; Attene, G.; Ardigo, L. P.; Dhahbi, W.; Chamari, K. (Research in Sports Medicine, 2015)
This study compared the effect of counter-movement-jump (CMJ)-based recovery on repeated-sprint-ability (RSA). Eighteen male footballers (16 ± 0 years, 65 ± 10 kg, 1.74 ± 0.10 m) performed three RSA-tests. RSA-1/-3 were performed according to standard procedures, while three CMJs (over 10') - as a potential fatigue-determinant and/or running mechanics interference - were administered during RSA-2 recoveries. RSA performance, exercise effort (fatigue index [FI], rating of perceived exertion [RPE], blood lactate concentration [BLa]), simple kinematics (steps number), vertical-jump characteristics (stretch-shortening-cycle-efficiency [SSCE] assessed before/after RSA) were investigated. ANOVA showed no differences between RSA-1,-3. During RSA-2, performance was lower than RSA-1/-3, while steps number did not change. During RSA-2, FI, BLa, RPE were higher than RSA-1/-3 (FI +21.10/+20.43%, P<0.05; BLa +16.25/+13.34%, P<0.05; RPE +12.50/+9.57%, P<0.05). During RSA-2, SSCE, as the CMJ/squat-jump-height-ratio, was not significantly different from RSA-1/-3. Passive recovery RSA allows better performance. Yet, RSA CMJ-based recovery is effective in increasing training load (FI, BLa, RPE) without perturbing running mechanics (simple kinematics, SSCE).